Topological Properties of Brain Structural Networks Represent Early Predictive Characteristics for the Occurrence of Bipolar Disorder in Patients With Major Depressive Disorder: A 7-Year Prospective Longitudinal Study - Liu, Haiyan; Zhao, Ke; Shi, Jiabo; Chen, Yu; Yao, Zhijian; Lu, Qing (Frontiers in Psychiatry, 2018)
Bipolar disorder (BD) and major depressive disorder (MDD) were associated with different brain functional and structural abnormalities, but the BD is hard to be distinguished from MDD until the first manic or hypomanic episode. The aim of this study was to examine whether the topological properties of brain structural network could be used to differentiate BD from MDD patients before their first manic/hypomanic episode. The diffusion tensor images were collected from 80 MDD patients and 53 healthy controls (HCs); 78 patients completed follow-up study lasting 7 years. Among them, 12 patients were converted to BD and 64 patients remained MDD. Topological properties of brain structural networks at baseline were compared among patients who converted to BD, patients who were not developed to BD, and HCs. Patients who converted to BD displayed reduced nodal local efficiency in the left inferior frontal gyrus compared with HCs and patients who have not converted to BD. There was no significant difference in the nodal global efficiency among the three groups. The findings suggest that the nodal local efficiency in the left inferior frontal gyrus could serve as a potential biomarker to predict the conversion of MDD to BD before the occurrence of first manic episode or hypomanic episode.